What should the doctor prescribe—formula diet or antidiabetics? Effectiveness of formula diet-based lifestyle intervention vs. pharmacological antiglycemic therapy on weight loss and HbA1c reduction in type 2 diabetes patients—a systematic review - Kempf, Kerstin; Röhling, Martin; Martin, Stephan (Frontiers in Endocrinology, 2025)
AimLifestyle intervention is the basis in type 2 diabetes therapy and leads, combined with formula diet, to substantial improvements in body weight and glycemic control up to diabetes remission. However, pharmacological therapies have also shown promising results. The aim of this systematic review was to compare the effects of large-sized formula diet-based lifestyle interventions vs. pharmacological interventions with glucagon-like peptide 1 receptor agonists (GLP-1 RAs), GLP-1, and glucose-dependent insulinotropic polypeptide (GIP) combinations and sodium glucose cotransporter-2 (SGLT-2) inhibitors on weight and HbA1c reduction in obese type 2 diabetes patients.MethodsLiterature searches were performed using PubMed for articles published until February 5, 2025. Primary and secondary outcomes were changes in weight [kg] and HbA1c [%] determined as estimated treatment difference (ETD) of intention-to-treat analyses (with a treatment policy approach).ResultsOf 1,409 identified articles, 54 articles describing 3 formula diet-based lifestyle interventions as well as 47 randomized, placebo-controlled pharmacological studies met our inclusion criteria including n=87.871 patients (32.8 ± 1.7 kg/m², 60 ± 4 years, 43 ± 7% women). Formula diet-based lifestyle intervention might more strongly reduce weight compared with pharmacological interventions with GIP/GLP-1 RAs or SGLT-2 inhibitors after <12 months (studies’ mean values: −5.6 vs. −2.6 kg) or ≥12-month intervention periods (−7.3 vs. −3.1 kg). Despite a trend for treatment superiority of pharmacological therapies in the short term (−0.9 vs. −0.6%), long-term HbA1c reduction was comparable between lifestyle and pharmacological interventions (−0.7%).ConclusionsThere is evidence that formula diet-based lifestyle intervention might improve weight loss to a greater extent than pharmacotherapies with comparable long-term glycemic control. Thus, formula diet-based lifestyle intervention might be a valid therapy option for obese patients with type 2 diabetes.